Adsorption of cadmium by biochar derived from municipal sewage sludge: Impact factors and adsorption mechanism. (September 2015) - Chen, Tan; Zhou, Zeyu; Han, Rong; Meng, Ruihong; Wang, Hongtao; Lu, Wenjing
Highlights: pH and biochar dosage are key factors for adsorption by sludge-derived biochar. Equilibrium temperature has weak adsorption effect. The mechanism of adsorption by biochar involves surface precipitation and ion exchange. Abstract: Static equilibrium experiments were carried out to investigate the impact factors and the mechanism of cadmium adsorption on biochar derived from municipal sewage sludge. An appropriate dosage of biochar is sufficient; in the experiment, 0.2% is the optimal dosage for the largest removal capacity, while the removal capacity of biochar reduces with the increasing dosage. pH is another dominant factor of the adsorption process. The removal capacity of biochar is lower than 20 mg·g −1 when the solution initial pH is lower than 2 pH units, comparatively retaining more than 40 mg·g −1 at the solution initial pH higher than 3 pH units. Temperature has weak influence on the adsorptive performance. The main mechanism of the adsorption process of biochar for cadmium mainly involves (1) surface precipitation by forming insoluble cadmium compounds in alkaline condition, and (2) ion exchange for cadmium with exchangeable cations in the biochar, such as calcium ions.